(untitled) (Agro Productividad, 2023)
Objective: To identify the role of women in the family patio agroecosystem and its relationship in the empowerment process, in two groups of women in the municipality of Medellín de Bravo, Veracruz, Mexico. Design/methodology/approach: The research carried out is qualitative-quantitative, of a constructionist nature, and is based on the Research-Action-Participatory process, through adaptation of the management model for natural resource management in family farming. Results: The psychometric results obtained in the Rosemberg Self-Esteem Scale indicate that the average response is 26.3, which indicates a normal self-esteem of women who work in the family patio agroecosystem, and positively impacts their human development, empowerment, and personal identity. Limitations on study/implications: The work of rural women in the family patio agroecosystem is not recognized, so it is important that it be made visible, mainly to them, and that they be empowered in their being, through their actions. Findings/conclusions: A total of 52 species were found, distributed among 15 fruit trees, 13 ornamental plants, 9 seasoning plants, 9 medicinal plants, 4 timber trees and only 2 vegetables. In the breeding of small species, 3 animal species are reported: 41 chickens, 2 pigs and 3 sheep.